CXCR Gene and its Association with Mastitis Resistance in Cattle- a Review - Dige, Mahesh. S.; Gowane, G. R.; Kokate, L. S.; Kumar B. V., Sunil; Bhushan, Bharat (International Journal of Bio-resource and Stress Management, 2023)
Genes associated with immune responses of mammary gland are potential genetic markers because of their importance in mastitis. Neutrophil functions are potential genetic markers for mastitis, as neutrophil migration from blood to the sites of infection is essential for resolution of most mastitis pathogens. The ability of neutrophils to migrate into infected tissues is dependent upon recognition of inflammatory mediators by neutrophil cytokines, chemokines, and complementary receptor. Among various chemokines, one of the important chemokine associated with leukocyte migration is interleukin-8 (IL-8). Being receiver and transmitter of the signal from IL-8 to downstream, the receptors of IL-8 (CXCR) are the important candidate genes for mastitis tolerance/ susceptibility study in the cattle herd.